Advantages of preoperative counseling with video for robotic rectal cancer surgery compared with conventional counseling: A randomized controlled trial. Issue 2 (26th November 2022) - Kasai, Shunsuke; Yamauchi, Shinichi; Tazawa, Miyako; Takaoka, Ayumi; Hanaoka, Marie; Iwata, Noriko; Masuda, Taiki; Tokunaga, Masanori; Kinugasa, Yusuke
Abstract: Purpose: Surgeons should provide patients with appropriate explanations before surgery and obtain informed consent. However, this process requires time and effort and can be a great burden. The purpose of this study was to compare preoperative counseling with video (VC) and conventional counseling (CC) for rectal cancer patients. Methods: Rectal cancer patients indicated for surgery were included between April 2021 and March 2022, and eligible patients were randomly assigned to the CC and VC groups. The primary outcomes were the comprehension, satisfaction, and anxiety levels, and the secondary outcome was the preoperative counseling time. This exploratory study protocol was registered with the UMIN Clinical Trials Registry (UMIN000038133). Results: We included 13 patients in the CC group and 17 in the VC group. All eligible patients were scheduled for robotic rectal cancer surgery. There were no significant differences between the two groups, including patients' general condition, preoperative diagnosis, and planned procedures. Although the comprehension, satisfaction, and anxiety test scores were not significantly different between the groups, the preoperative counseling time was significantly shorter in the VC group than in the CC group (20 vs. 35 minutes, P  = .002). A 4‐year college degree significantly increased the counseling time, whereas VC significantly decreased it. Conclusion: Using videos in preoperative counseling for rectal cancer patients is useful. This novel method could reduce the burden on surgeons during preoperative counseling in the era of robotic surgery and work style reforms.